الاستغاثة الشرعية والبدعية في اليوتيوب: دراسة تحليلية - الظفيري، تركي بن خالد رشيد (جامعة الأمير سطام بن عبدالعزيز, 2016)
This thesis addressed Shari’a compliant and innovated call for help in YouTube The objective: Find out the concept of call for help and different types of Shari’a compliant and innovated call for help, and specify their status in YouTube Research. Methodology: descriptive and inductive approach. The most important results: The results showed almost same number of watching of videos of Shari’a compliant and innovated call for help. However, regarding the positive interaction with the comments and preferences it was clearly tends to Shari’a compliant videos. Main recommendations: to educate followers of YouTube videos, to support Shari’a compliant videos through watching, like and comment thereon. The study also recommended the importance of the establishment of studies Centers to conduct researches about doctrine issues in various media.
يعنى هذا البحث بالاستغاثة الشرعية والبدعية في اليوتيوب وتهدف إلى: معرفة مفهوم الاستغاثة وأنواع الاستغاثة المشروعة والبدعية، ومعرفة واقعها في اليوتيوب. منهج البحث: المنهج الاستقرائي والوصفي. ومن أهم نتائج البحث: أظهرت النتائج تقارباً بين عدد مشاهدات مقاطع الاستغاثة الشرعية والبدعية، أما من حيث التفاعل الإيجابي مع التعليقات والتفضيلات كان يميل بوضوح إلى المقاطع الشرعية. ومن أهم التوصيات: توعية المتابعين لليوتيوب بدعم المقاطع التي تدعو للمنهج الشرعي بالمشاهدة والتفضيل لها والتعليق عليها، كما أوصت الدراسة إلى أهمية إنشاء مراكز دراسات تبحث المسائل العقدية في وسائل الإعلام المختلفة.
Keywords: الشريعة الإسلامية -- الأحكام الشرعية -- العقيدة الإسلامية -- الاستغاثة -- اليوتيوب